Vpliv daljšega zdravljenja z inhalacijskimi glukokortikoidi na rast in telesno težo otrok, starih 6 do 24 mesecev - Besednjak-Kocijančič, Lilijana (Zdravniški vestnik, 2005)
Background. Inhaled glucocorticoids are drugs of the first choice for the asthma treatment Their growth suppressive potential is well known. It has beensuggested that it may wane off during the first year of treatment. It has been also suspected that asthmatic children might become overweight/obese after asthma therapy. The aim of this prospective study was to assess the influence of long-term treatment with fluticasone propionate (FP) on body weight and growth in asthmatic children aged 6 to 24 month. Methods. 26 pairs of children of the same age with birth weight > 3000 g took part in 12-month parallel group trial. Group A consisted of children mith mild persistent asthma treated for the first time. Inhaled FP 100 ug twice daily was used. Group B consisted of healthy children. In each group there were 17 males and 9females. Weight and height data during 6-month prior to enrolment in the trial were retrospectively collected from the notes. Length and weight of bothchildren from a pair were measured on the same day frorn day 1 every 3 month up to a year on the same measuring instrument SPSS software 10.0 was used for statistical analyses. t-tests were employed for between-group analyses. Results. Mean weight was greater for 156g in group A (t = 0.29, p = 0.77, DF:24), and the mean length increase was greater for 0.72 cm in group B (t = -1.06, p = 0.30, DF:24). The differences between group A and B were not statistically significant. A marked decrease in mean length difference from 0.26 in the first to 0. 09 cm in the last quarter of the study was observed. Conclusions. Long-term treatment with inthaled glucocorticoids (1OO ug FP twice daily) is safe in spite to their suppressive effect on growth. The growth suppressive pote ratial of inhaled glucocorticoids is decreasing duringthe treatment. There is a no sigraificant influence on body weight.
Keywords: Administration, Inhalation; Asthma; Astma; baby; Body Height; Body Weight; child; Child Development; Dojenček; Drug Therapy; Glucocorticoids, Synthetic; Glukokortikoidi umetni; Infant; inhalatorji; otroci; Otrok, razvoj; rast; Telesna teža; Telesna višina; therapy; Zdravilo, inhalacijska uporaba; zdravljenje